FRI0481 Microvascular Modifications in Very Early Systemic Sclerosis Patients. (10th June 2014) - Bruni, C.; Guiducci, S.; Bellando Randone, S.; Lepri, G.; Blagojevic, J.; Radicati, A.; Matucci Cerinic, M.
Abstract : Background: Great interest is devoted today to patients with very early diagnosis of systemic sclerosis (VEDOSS), characterized by the presence of Raynaud phenomenon (RP), puffy fingers, Antinuclear antibodies (ANA), plus the presence of disease related autoantibodies (anti-centromere – ACA – and antiTopoisomerase I – ATA) and/or nailfold videocapillaroscopy (NVC) scleroderma pattern [1, 2]. In established SSc, NVC is today considered an outcome measure [3]. Objectives: To describe microvascular modifications in VEDOSS patients and to retrospectively evaluate te effectiveness of NVC in monitoring the evolution of microvascular disease. Methods: Patients with RP attending our outpatient clinics from March 2010 to October 2013 were enrolled. Autoantibodies were tested and NVC was performed at baseline and at follow-up an optical probe equipped with 200x lens. Giant capillaries, micro-haemorrhages, capillary loss and ramified/bushy capillaries were searched in NVC images and then clustered/scored according to the medium value of the alteration, as following: 0% present, score 0; from 0% to 33%, score 1; from 33% to 66%, score 2; over 66%, score 3 [4]. Scores given to each parameter were summed and compared between baseline and follow-up assessment: a decrease of the total score of at least 2 points was considered as improvement, an increase of at least 2 points as worsening, otherwise as stable. Results: 167 patients were enrolled (18 males, mean age 51±15 years, 10±8 years since RP onset), with ANA positive in 96/167 (57.5%), ACA and ATA in 41/167 (24.5%) and 17/167 (10.2%) respectively. On NVC, giant capillaries were found in 62/167 (37.1%), haemorrhages in 72/167 (43.1%), loss of capillaries in 2/167 (1.2%) and ramified/bushy capillaries in 10/167 (5.9%). At baseline, giant capillaries and haemorrhages were associated with ANA plus ACA/ATA positivity ( p <0.01), also confirmed for VEDOSS patients. Comparing baseline to follow up NVC evaluation (mean time 1.4±0.5 years), the presence of ANA plus ACA/ATA showed a trend to association (p=0.07) with worsening of microvascular involvement, which was statistically significant when VEDOSS criteria were satisfied (p<0.05); a trend toward improvement was seen in ANA negative patients (p=0.08). Conclusions: NVC confirms its ability in detecting capillary modification in VEDOSS patients, as well as its effectiveness in monitoring microvascular disease evolution in time. References: Avouac J, Fransen J, Walker UA et al. Preliminary criteria for the very early diagnosis of systemic sclerosis: results of a Delphi Consensus Study from EULAR Scleroderma Trials and Research Group, Ann Rheum Dis 2011Mar;70:476-81. Minier T, Guiducci S, Bellando-Randone S et al. Preliminary analysis of the Very Early Diagnosis of Systemic Sclerosis (VEDOSS) EUSTAR multicentre study: evidence for puffy fingers as a pivotal sign for suspicion of systemic sclerosis. Ann Rheum Dis.2013 Aug 12. Cutolo M, Sulli A, Pizzorni C et al. Capillaroscopy as an Outcome Measure for Clinical Trials on the Peripheral Vasculopathy in SSc-Is It Useful? Int J Rheumatol 2010. Sulli A, Secchi ME, Pizzorni C, Cutolo M.Scoring the nailfold microvascular changes during the capillroscopic analysis in systemic sclerosis patients.Ann Rheum Dis.2008 Jun;67(6):885-7.Epub 2007 Nov 23 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2957